Sistem Kontrol dan Monitoring Prototype Smart Green House pada Tanaman Stroberi menggunakan Logika Fuzzy berbasis Aplikasi Cayenne - Yazid Ananda; Mochammad Hannats Hanafi Ichsan; Agung Setia Budi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2023)
Controlling the air quality of strawberry plants in a smart greenhouse prototype must be of great concern to strawberry farmers in order to get maximum yields. Air quality parameters that must be monitored, for example, are air temperature and air humidity as parameters that can affect the viability of strawberry plants. Given these problems, there is a need for research related to a system that can help answer these problems, namely the Smart Green House Prototype Control and Monitoring System on Strawberry Plants Using Fuzzy Logic Based on the Cayenne Application. The method used is the Mamdani fuzzy model to assist the control system in controlling air quality parameters in the smart greenhouse prototype, namely temperature and humidity parameters. The microcontroller used is Wemos D1R2 which can connect to the wifi network and can connect to Cayenne so that it can be monitored via Cayenne. The temperature and humidity sensor used is the DHT 22 sensor and based on the results of the test, it is obtained an error value range of 20,75% for temperature, while for humidity the DHT 22 sensor produces an error value of 18,7%. The test was carried out nine times in three conditions, namely cold, normal, hot for temperature and low, normal, high for humidity. The smart greenhouse prototype was also tested how effective the system is in controlling the environment by conducting experiments using actuators and without actuators. The results obtained from testing using the actuator, the temperature inside the smartgreenhouse can decrease by 2.13Â°C and humidity can increase by 5.1%. The second test was carried out without an actuator, so the temperature rose by 9.82Â°C and the humidity decreased by 22.16%.